THE SOCIALIZATION OF SMART BUILDING IMPLEMENTATION IN LIGHTING SYSTEM - Barnadi, Yudi; Mayang, Ajeng; Suryana, Ase; Mayang, Ajeng (CENTRAL ASIA AND THE CAUCASUS, 2022)
Smart building is an application of an automatic control system to a building. Where this system has been arranged using a neatly structured algorithm. Almost all parts or building components can be managed automatically. Therefore, it can also be called a Building Automation System or BAS. The working principle of this smart building is the integration of various components in the building. From these installed components, apart from being able to be set automatically, there is also communication between components. In general, the method used for smart buildings is to use sensors. The larger the building, of course, the higher the energy required. If the property management still manages it manually, there is a tendency for a factor to be missed This makes energy use more wasteful. In addition to lighting and HVAC, many components of buildings use electricity. Such as pumps, dispensers, computers, televisions, and so on. It should be off or not connected to electricity when the building is empty.